2020
DOI: 10.1038/s41467-020-16252-2
|View full text |Cite
|
Sign up to set email alerts
|

Finding the equilibrium of organic electrochemical transistors

Abstract: Organic Electrochemical Transistors are versatile sensors that became essential for the field of organic bioelectronics. However, despite their importance, an incomplete understanding of their working mechanism is currently precluding a targeted design of Organic Electrochemical Transistors and it is still challenging to formulate precise design rules guiding materials development in this field. Here, it is argued that current capacitive device models neglect lateral ion currents in the transistor channel and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 27 publications
1
92
0
Order By: Relevance
“…The 2D device model used here deviates from this assumption and calculates the ion concentration under the assumption that cations reach their equilibrium, [ 30 ] which leads to a significantly different ion distribution along the transistor channel. To test if the geometric scaling law described by Equation (3), can be reproduced by the device model used here, the transconductance as a function of dL is plotted in Figure a.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 2D device model used here deviates from this assumption and calculates the ion concentration under the assumption that cations reach their equilibrium, [ 30 ] which leads to a significantly different ion distribution along the transistor channel. To test if the geometric scaling law described by Equation (3), can be reproduced by the device model used here, the transconductance as a function of dL is plotted in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…However, as recently shown, the assumption of a gate capacitance does not describe the equilibrium state of the OECT. [ 30 ] A 2D model was developed that treats ion and hole currents consistently, ensuring the the device is reaching its equilibrium. Based on this model, it was shown that the ion concentration inside the transistor channel is not proportional to the channel potential, that is, it cannot be described by a capacitive term.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 83,84,88,89 ] The presence of both ionic and electronic currents in conjugated polymer–polyelectrolyte systems further complicates interpretation, with many ongoing attempts to accurately model this behavior. [ 89–92 ] Tybrandt et al. recently proposed a two‐phase model based on drift‐diffusion equations.…”
Section: Fundamental Mechanismsmentioning
confidence: 99%